Fertigation Nutrient Sources and Application Considerations for Citrus - Brian Boman; Tom Obreza (EDIS)
This is Circular 1410, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2002.